Invitro Antioxidant and Cytotoxic Potential of Ficus carica L. and Olea europeae L. Against Cervical Cancer - Widyaningrum, Naniek; Hussaana, Atina; Puspitasari, Nesya Ayu (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
INTRODUCTION:Cervical cancer is a malignant infectious disease caused by Human Papilloma Virus (HPV) in the cervix. Fig and olive oil containing flavonoid has been shown to have antioxidant and anticancer activity.OBJECTIVE:This study aimed to evaluate antioxidant and cytotoxic activity of combined Ficus carica L. and Olea europeae L. against HeLa cervical cancer cells.METHODS: This is an experimental study with a post-test only control group design. The HeLa cells were divided into 5 groups: fig extract, olive oil, combined fig extract and olive oil (at the ratio of 1:3, 1:1, 3:1), positive control (doxorubicin). The cytotoxic and antioxidant activity were evaluated by using MTT Assay and DPPH, respectively. The cytotoxic results were analyzed using probit and antioxidant activity was analyzed by using linear regression to obtain IC50 values.RESULTS:The IC50 cytotoxic of fig extract, olive oil, combined fig extract and olive oil (at the ratio of 1:3, 1:1, 3:1) with positive control (doxorubicin) were 13063,915 Î¼g/mL, 679,593 Î¼g/mL, 1562,356 Î¼g/mL, 746,923Î¼g/mL, 563,626 Î¼g/mL and 13,707 Î¼g/mL respectively. The IC50 antioxidant of fig extract, olive oil, and combination of fig extract and olive oil (3:1) was 105.9272 ppm, 23.1276 ppm, and 21,0689 ppm respectively.CONCLUSION:The combination of fig extract and olive oil (3:1) was shown to have the highest antioxidant and cytotoxic activity against HeLa cervical cancer cells.